Tailored resection of spinal dumbbell schwannomas using transforaminal and modified epidural trans dural sleeve approaches with hemilaminectomy - Wu, Qiaowei; Rao, Yihua; Zhang, Xiaohai; Shen, Yulong; Wu, Dongxu; Shu, Zhicheng; Liu, Kebo; Luo, Kun; Yao, Jing; Liu, Jianbiao; Li, Weifeng; Yang, Changyong; et al. (Frontiers in Surgery, 2025)
Background and purposeSurgical resection of dumbbell-shaped spinal schwannomas, which involve both intra-extradural and intra-extraspinal components, presents significant technical challenges. This study aimed to evaluate the safety and efficacy of the transforaminal and modified epidural trans dural sleeve approaches with hemilaminectomy without dural incision for the tailored resection of spinal dumbbell-shaped tumors in comparison with conventional laminectomy.MethodsThis was a retrospective, observational cohort study. Between May 2017 and November 2024. A total of 44 patients with extra-intraspinal dumbbell-shaped tumors who underwent tumor resection were included in the analysis. Procedure-related data, postprocedural serious adverse events (SAEs), clinical and imaging outcomes were evaluated.ResultsAll patients (44 tumors) were successfully treated, of which 20 patients were treated through the epidural trans-dural sleeve approach (epidural approach group) and 24 patients were treated through the conventional laminectomy and dural incision (conventional approach group). Gross total resection was performed in 95.5% (42/44) patients, with 2 cases of residual tumor in the conventional approach group. A total of 12 (27.3%) patients experienced at least one SAE before discharge, including 3 (15.0%) in the epidural approach group and 9 (37.5%) in the conventional approach group (P = 0.095). Blood transfusions were performed in 10 (41.7%) patients in the conventional approach group, and no patients were required in the epidural approach group (P = 0.003). Multivariate analysis revealed that intraprocedural estimated blood loss ≥ 350 mL was significantly associated with SAEs during hospitalization (OR: 6.6; 95%CI: 1.5–29.7; P = 0.014). During the follow-up duration of 28.0 (9.5, 51.0) months, 42 patients were classified as ASIA grade E, and 2 as grade D. No tumor recurrence was detected during the imaging follow-up.ConclusionEpidural trans-dural sleeve approach can be a safe and effective method for treating spinal dumbbell-shaped tumors, with relatively lower intraprocedural blood loss and transfusion rates compared to conventional techniques. Intraprocedural estimated blood loss ≥ 350 mL was significantly associated with SAEs during hospitalization.